2023
DOI: 10.1002/pd.6393
|View full text |Cite
|
Sign up to set email alerts
|

First‐trimester screening strategies: A balance between costs, efficiency and diagnostic yield

Abstract: What's already known about this topic?� An early scan at 11-13 + 6 weeks offers the ideal opportunity for a first detailed anatomical assessment of the fetus.� Non-invasive prenatal testing (NIPT) is superior to the combined test to screen for common trisomies, especially trisomy 21, in both singleton and twin pregnancies. What does this study add?� In first-trimester screening strategies based on NIPT and ultrasound, many factors must be considered when choosing how to combine the two methods. We propose four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Future research should focus on the right moment of FTAS, before or after cfDNA testing and evaluate its additional healthcare costs. 32 However, a recent study showed that FTAS before cfDNA testing is a more cost-effective strategy for noninvasive prenatal aneuploidy screening compared to cfDNA alone. 33…”
Section: Discussionmentioning
confidence: 99%
“…Future research should focus on the right moment of FTAS, before or after cfDNA testing and evaluate its additional healthcare costs. 32 However, a recent study showed that FTAS before cfDNA testing is a more cost-effective strategy for noninvasive prenatal aneuploidy screening compared to cfDNA alone. 33…”
Section: Discussionmentioning
confidence: 99%
“…The ongoing debate about how best to integrate NIPT with ultrasound and the combined first trimester screen is addressed in a commentary by Bardi and colleagues 7 . It is notable that the rapid diffusion of NIPT, stimulated by important financial interests, has not been emulated by first trimester ultrasound screening.…”
Section: Figurementioning
confidence: 99%
“…Research continues to bring new insights on the diagnostic ability of the early ultrasound scan: the fetal heart, 11 the central nervous system 12,13 skeletal dysplasias 14 and increased nuchal translucency 15 . Also, among the first trimester screening strategies for congenital anomalies discussed by Bardi et al., early anatomical assessment occupies a central role, from the most advanced to more traditional screening menus 7 …”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations